The Effect Of Price Discounts and Product Quality On Skin Care Consumers' Buying Interest: Case Study on Vaseline Body Lotion Consumers in Bogor City - Angelica Putri; Morita Morita (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
A recent phenomenon that has occurred in society, including in the city of Bogor, is that more and more consumers are interested in using body care products. Vaseline is a company that produces quality body care and beauty products. However, with the increasing number of competitors, Vaseline products are starting to become less popular with consumers. The objectives of this research are (1) To determine the effect of price cuts made by Vaseline products on consumer buying interest in the city of Bogor, (2) To find out the effect of Vaseline product quality on consumer buying interest in the city of Bogor, (3) To find out the effect of price cuts and Vaseline product quality together on consumer buying interest in the city of Bogor. Data was collected using a questionnaire. The number of respondents in this study is 110 respondents who are familiar with and have used Vaseline products in Bogor. The research data was processed using SPSS. The results of this study are as follows: (1) Discount Offers (X1) partially influence Purchase Intention (Y) with the t-count value greater than the t-table (4.141 > 1.659), thus H0 is rejected and H1 is accepted; (2) Product Quality (X2) partially influences Purchase Intention (Y) with the t-count value greater than the t-table (4,566 > 1,659), thus H0 is rejected and H2 is accepted; (3) Discount Offers and Product Quality together have a positive and significant influence on Purchase Intention with the F-count value greater than the F-table (77,699 > 3.08), thus H0 is rejected and H3 is accepted. Therefore, it can be concluded that Discount Offers and Product Quality contribute to Consumer Purchase Intention, with an R-Square value of 59.2%, and the remaining 40.8% is explained by other variables. Keywords: Price Discounts, Product Quality, Consumer Purchase Interest